Slang Words in How to Train Your Dragon Movie - Luh Putu Mayla Cempaka Artatik; I Gusti Agung Istri Aryani; Ni Ketut Alit Ida Setianingsih (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study examines the use of slang words in How to Train Your Dragon (2010). Slang represents an informal language variety that reflects emotions, identity, and social relationships in everyday communication. This study aims to identify the types of slang used by the characters and analyze their meanings based on Allan and Burridge’s theory of slang and Leech’s theory of meaning. A descriptive qualitative method was employed using the movie dialogues and transcript as the data source. Data were collected by repeatedly watching the movie, examining the transcript, identifying slang expressions, and analyzing their contexts. The findings indicate that the characters use various types of slang, with imitative slang occurring most frequently, followed by clipping, fresh and creative, and flippant slang. Regarding meaning, the slang expressions predominantly convey social, affective, connotative, conceptual, thematic, and reflective meanings depending on the conversational context and interpersonal relationships. The study concludes that slang functions not only as informal language but also as a means of expressing emotions, creating humor, strengthening solidarity, and constructing character identity. The findings also demonstrate that contextual factors play a crucial role in interpreting slang and contribute to the authenticity and realism of the movie’s dialogues.